Circumstances to Be Clarified under the Investigation of Interference into Law Enforcement Officer’s Activity - V. O. Gusieva (Law and Safety)
The author has substantiated the need to establish the circumstances to be clarified and has determined their significance during the investigation. It has been emphasized that the circumstances to be clarified include the circumstances to be proved in criminal proceedings, criminal and forensic characteristics of a criminal offense.